On elliptic systems in Hörmander spaces - Murach, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We study a linear system of pseudodifferential equations uniformly elliptic in Petrovskii’s sense in the Hilbert scale of Hörmander functional spaces defined in ℝ_n. An a priori estimate is proved for the solution of the system and its interior smoothness in this scale of spaces is investigated. As an application, we establish a sufficient condition for the existence of continuous bounded derivatives of the solution.